Utilizing the E-Book System in Supporting Students’ Literacy and Independent Learning - Amrina Amrina; Sri Nur Rahmi (Scientechno: Journal of Science and Technology, 2024)
The development of the E-Book system in supporting learning literacy is very beneficial for students in the era of globalization. In today’s era of globalization, it has utilized the E-Book system in various schools in the learning system. The use of E-Books in learning has a positive impact on the present and the future. This study aims to understand the concept of utilizing the E-Book system in supporting students’ literacy and independent learning by utilizing the E-Book system in education and to find out the extent of the development of the E-Book system in education. So that teachers and students can use this E-Book system as a means of learning. The method used by the researcher in conducting this study is quantitative, with data obtained through disseminating questionnaires online using Google Forms. The word was processed using the SPSS application by statistical analysis through the ANOVA test; after completing the data test, the researcher presented the data in the form of graphs and tables containing respondents. The results of this study show that the introduction of an offline-based E-Book system will be able to support the literacy and independent learning of students in the world of education. Using the E-Book system in education brings various benefits, such as increasing student participation and supporting the understanding of complex concepts. Learning that utilizes the E-Book system has progressed compared to learning that still uses its own learning method, and cannot compete in the world of education. This study concludes that utilizing the E-Book system, especially independent learning, positively impacts education. The use of the E-Book system is expected to build interactive and effective learning resources. The use of the e-book system in education shows that it can improve the quality of learning and provide advantages in the educational process.